The ghoul vendetta - Shearin, Lisa (Shearin, Lisa. SPI Files novel., 2017)
The agents of Supernatural Protection & Investigations (SPI) are paid to keep the peace. But that's not so easy when an endless evil threatens to tear that peace to pieces. A vampire gangster's nephew is abducted off his yacht by a bunch of low-rent Creatures from the Black Lagoon. A slew of banks are knocked over by what looks like the cast of Night of the Living Dead. All of this may seem like the movies, but, I promise you, it's not. I'm Makenna Fraser, seer for SPI, and I know the culprits aren't wearing disguises or makeup. They're real. Deadly real. Especially their leader - an ancient shapeshifter who leaves a trail of chaos and blood in his wake. Now he's taken my partner, Ian - and his intentions aren't pretty. The worst part? This is only the beginning...the beginning of the end of the human race.